Integrated pan-cancer analysis and experimental verification of the roles of tropomyosin 4 in gastric cancer - Guo, Qijing; Zhao, Linglin; Yan, Nan; Li, Yan; Guo, Cuiping; Dang, Shengyan; Shen, Xianliang; Han, Jianfang; Luo, Yushuang (Frontiers in Immunology, 2023)
Objective To investigate the function of tropomyosin 4 (TPM4) using pan-cancer data, especially in gastric cancer (GC), using comprehensive bioinformatics analysis and molecular experiments. Methods We used UCSC Xena, The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression Project (GTEx), TIMER2.0, GEPIA, cBioPortal, Xiantao tool, and UALCAN websites and databases for the extraction of pan-cancer data on TPM4. TPM4 expression was investigated with respect to prognosis, genetic alterations, epigenetic alterations, and immune infiltration. RNA22, miRWalk, miRDB, Starbase 2.0, and Cytoscape were used for identifying and constructing the regulatory networks of lncRNAs, miRNAs, and TPM4 in GC. Data from GSCALite, drug bank databases, and Connectivity Map (CMap) were used to analyze the sensitivity of drugs dependent on TPM4 expression. Gene Ontology (GO), enrichment analyses of the Kyoto Encyclopedia of Genes and Genomes (KEGG), wound healing assays, and (Matrigel) transwell experiments were used to investigate the biological functions of TPM4 in GC. Result The findings of the comprehensive pan-cancer analysis revealed that TPM4 has a certain diagnostic and prognosis value in most cancers. Alterations in the expression of TPM4, including duplications and deep mutations, and epigenetic alterations revealed that TPM4 expression is related to the expression of DNA methylation inhibitors and RNA methylation regulators at high concentrations. Besides, TPM4 expression was found to correlate with immune cell infiltration, immune checkpoint (ICP) gene expression, the tumor mutational burden (TMB), and microsatellite instability (MSI). Neoantigens (NEO) were also found to influence its response to immunotherapy. A lncRNA-miRNA -TPM4 network was found to regulate GC development and progression. TPM4 expression was related to docetaxel,5-fluorouracil, and eight small molecular targeted drugs sensitivity. Gene function enrichment analyses revealed that genes that were co-expressed with TPM4 were enriched within the extracellular matrix (ECM)-related pathways. Wound-healing and (Matrigel) transwell assays revealed that TPM4 promotes cell migration and invasion. TPM4, as an oncogene, plays a biological role, perhaps via ECM remodeling in GC. Conclusions TPM4 is a prospective marker for the diagnosis, treatment outcome, immunology, chemotherapy, and small molecular drugs targeted for pan-cancer treatment, including GC treatment. The lncRNA-miRNA-TPM4network regulates the mechanism underlying GC progression. TPM4 may facilitate the invasion and migration of GC cells, possibly through ECM remodeling.